KEYAKINAN DIRI REMAJA BERBASIS HEALTH BELIEF MODEL TERHADAP VAKSINASI COVID-19 SETELAH EDUKASI DENGAN MEDIA BUKU SAKU INFOVAKSIN ELEKTRONIK - Niken Ayu Widhayanti; Mujito .; Agus Khoirul Anam (Poltekkes Kemenkes Malang, 2022)
TEENAGERS' SELF EFFICACY BASED ON HEALTH BELIEF MODEL AFTER VACCINATION COVID-19 EDUCATION WITH POCKETS INFOVAKSIN ELECTRONIC MEDIA BOOKS Abstract: A covid 19 vaccination is a preventive measure by putting in biological products containing antigens when given to a person will result in active immunity to covid 19. The purpose of this study is to know the self confidence of a health based youth model on vaccination covid 19 after the education with the media of the electronic infovaccine pocketbook. The research design used was a pre experimental one group pretest posttest design with a population of all students of class XII MAN Blitar City, totaling 324 students who met the inclusion criteria. The sampling technique used was purposive sampling, with a sample size of 33 teenagers. Data were analyzed using the Paired Sample T Test with an error rate of a kurang dari 0.05. The results of measuring self confidence are 55 percent sure (pretest) and 82 percent confident (posttest) with an average self confidence value of 57 (pretest) and 67 (posttest). The results of the statistic test have found a value of p 0,000, which means that education using the media's electronic infovaccine pocket book influence the self confidence based health model of vaccination covid 19. It is hoped that health educators and health-care programs apply to electronic book media, followed by the process of group discussion and individual task to discuss Covid 19 prevention and control materials to change the teen's view and confidence to initiate a Covid-19 vaccination. Keywords: education, electronic books, teenagers, vaccination covid-19